Answer :

Given

a_{n} = 0, n = ?

3^{rd} term = 4

⇒ a + (3-1)d = 4 → __1__

9^{th} term = 73

⇒ a + (9-1)d = -8 → __2__

By subtracting the both equations we will get ‘d’

(a +2d) – (a+8d) = 4 – (-8)

-6d = 12

d = -2

By substituting “d” in equation __1__

a +2d = 4

a + (-2)2 = 4

a = 8

a_{n} = a+(n-1)d

0 = 8+(n-1)(-2)

-8 = (n-1)(-2)

4 = n-1

n = 5

∴ 0 is the 5^{th} term in the series.

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Find the</sAP- Mathematics

Find the</sAP- Mathematics

Find the reAP- Mathematics

Find the reAP- Mathematics

Find the reAP- Mathematics

Find the reAP- Mathematics

If the 3<suAP- Mathematics

Find the reAP- Mathematics

Two APs havAP- Mathematics

For what vaAP- Mathematics